Assessing the potential for liquid solvents from X-ray sources: considerations on bodies orbiting active galactic nuclei - Rodener, Daniel; Schäfer, Myriam; Hausmann, Michael; Hildenbrand, Georg Lars (Galaxies, 2022)
We aim to establish a rough first prospect on the potential of certain biorelevant solvents (water, ammonia, and methane) being present in liquid form inside the uppermost few meters of several modeled rocky and icy surfaces of hypothetical bodies orbiting active galactic nuclei (AGNs) and investigate under which constraints this might occur. For this, we adjust and average X-ray spectra from a sample of 20 Type-1 Seyfert galaxies to calculate the mean snowline of the sample used. We then vary the hypothetical body’s orbit between 10% and 100% of the snowline radius and calculate a sub-surface attenuation within four different model surface compositions for each. We then use this as a continuous source term for a thermal model. Example bodies are systematically investigated with sizes between 1/30 and 20 earth radii, with further variations also considered (such as possible bound rotation), to end up with a perspective of solvent phases under a wide slew of different conditions. We find that liquid solvents are possible under a multitude of parameters, with temperature being the main constraint to liquid water whereas body size and pressure are the main constraint to liquid methane and ammonia.